2012
DOI: 10.1103/physrevlett.108.230602
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Fractional Lévy Kinetics for Cold Atoms Diffusing in Optical Lattices

Abstract: Recently, anomalous superdiffusion of ultracold 87Rb atoms in an optical lattice has been observed along with a fat-tailed, Lévy type, spatial distribution. The anomalous exponents were found to depend on the depth of the optical potential. We find, within the framework of the semiclassical theory of Sisyphus cooling, three distinct phases of the dynamics as the optical potential depth is lowered: normal diffusion; Lévy diffusion; and x∼t(3/2) scaling, the latter related to Obukhov's model (1959) of turbulence… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
117
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 106 publications
(123 citation statements)
references
References 38 publications
(58 reference statements)
6
117
0
Order By: Relevance
“…For α > 3, the usual Green-Kubo formula (4) holds. We can thus identify three different diffusion phases [49]: normal diffusion with hx 2 ðtÞi ∼ t when α > 3, anomalous superdiffusion with hx 2 ðtÞi ∼ t 4−α when 1 < α < 3, and Richardson-like diffusion with hx 2 ðtÞi ∼ t 3 when α < 1, which is known from turbulence [50] and has recently been observed as a transient behavior in ordinary Brownian motion [51].…”
Section: (28)mentioning
confidence: 99%
“…For α > 3, the usual Green-Kubo formula (4) holds. We can thus identify three different diffusion phases [49]: normal diffusion with hx 2 ðtÞi ∼ t when α > 3, anomalous superdiffusion with hx 2 ðtÞi ∼ t 4−α when 1 < α < 3, and Richardson-like diffusion with hx 2 ðtÞi ∼ t 3 when α < 1, which is known from turbulence [50] and has recently been observed as a transient behavior in ordinary Brownian motion [51].…”
Section: (28)mentioning
confidence: 99%
“…However many systems do not meet this requirement [2], for example Lévy fat-tailed processes [7][8][9], where the decay rate is a power-law. This is the case for a cloud of atoms undergoing Sisyphus laser-cooling [10], where both theoretically [11,12] and experimentally [13], it was shown that the central part of the spreading particle packet is described by the Lévy CLT [14]. The latter deals with the sum of independent identically-distributed random variables, but unlike the classical Gaussian CLT, here the summands' own distribution is heavy-tailed.…”
mentioning
confidence: 99%
“…Lévy walk is a fundamental notion in physics and biology [1] with numerous applications including the transport of light governed by Lévy statistics [2], anomalous superdiffusion of cold atoms in optical lattices [3], T-cell motility in the brain [4], endosomal active transport within living cells [5]. In the last few years, the interest in the Lévy walk models increases rapidly in the context of Lévy flight foraging hypothesis according to which a Lévy transport is optimal to search for randomly located objects [6].…”
mentioning
confidence: 99%